Non-contiguous finished genome sequence and description of Bartonella florenciae sp. nov. Issue 1 (July 2013) - Mediannikov, Oleg; Karkouri, Khalid; Robert, Catherine; Fournier, Pierre-Edouard; Raoult, Didier
Abstract Bartonella florenciae sp. nov. strain R4T is the type strain ofB. florenciae sp. nov., a new species within the genusBartonella . This strain, whose genome is described here, was isolated in France from the spleen of the shrewCrocidura russula .B. florenciae is an aerobic, rod-shaped, Gram-negative bacterium. Here we describe the features of this organism, together with the complete genome sequence and its annotation. The 2, 010, 844 bp-long genome contains 1, 909 protein-coding and 46 RNA genes, including two rRNA operons.